The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/jobm.201300350
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and kinetic properties of halostable endoglucanase from Aspergillus fumigatus ABK9

Abstract: An endoglucanase from Aspergillus fumigatus ABK9 was purified from the culture extract of solid-state fermentation and its some characteristics were evaluated. The molecular weight of the purified enzyme (56.3 kDa) was determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, zymogram analysis and confirmed by MALDI-TOF mass spectrometry. The enzyme was active optimally at 50 °C, pH 5.0 and stable over a broad range of pH (4.0-7.0) and NaCl concentration of 0-3.0 M. The pKa1 and pKa2 of the ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…The culture of Streptomyces sp. ssr-198 was grown in an optimized sterilized medium (untreated paddy straw 18.39 g, peptone 1.0 g, K 2 HPO 4 5.0 g, (NH 4 )SO 4 . For inoculum preparation, the 24 h old cultures grown in nutrient broth were centrifuged and re-suspended in normal saline to achieve an OD of 0.8.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The culture of Streptomyces sp. ssr-198 was grown in an optimized sterilized medium (untreated paddy straw 18.39 g, peptone 1.0 g, K 2 HPO 4 5.0 g, (NH 4 )SO 4 . For inoculum preparation, the 24 h old cultures grown in nutrient broth were centrifuged and re-suspended in normal saline to achieve an OD of 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…and other enzymes from different microorganisms to produce high titer of a synergistically acting enzyme cocktail. Besides T. reesei , many other filamentous fungi like T. viride , Humicola insolens , Penicillium verruculosum , A. japonicus , A. fumigatus , Acremonium cellulolyticus are also known to be good producers of different cellulolytic enzymes .…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current study were in good agreement with those reported for most of the endoglucanase from Aspergillus strains, such as A. terreus DSM 826, 42 A. awamori VTCC-F099, 38 A. usamii E001 7 and A. fumigatus ABK9. 20 However, a high thermal stability (70 °C) was also reported for endoglucanases from T. aurantiacus 43 and A. fumigatus MKU1. 3 The differences in thermal stability indicated the different molecular properties of the enzymes, including the bonding that stabilizes in the structures and the conformations among the various species.…”
Section: Discussionmentioning
confidence: 95%
“…The predicted molecular weight of the endoglucanase from A. fumigatus DBiNU-1, as confirmed by SDS-PAGE analysis, was approximately 48 kDa, which was distinct from other endoglucanases from other Aspergillus strains, e.g., A. terreus M11 (25 kDa), 37 A. awamori VTCC-F099 (32 kDa), 38 A. fumigatus KMU1 (35 kDa), 3 A. oryzae AG1 (45 kDa), 39 A. usamii E001 (24 kDa), 7 and A. fumigatus ABK9 (56 kDa). 20 Many glycoside hydrolases such as GH7, GH12, GH16 and AA9 have a modular structure that consists of a catalytic domain and a substrate-binding domain. 40 The Swiss-PdbViewer ( http://www/expasy.org/spdbv ) was used to predict the three-dimensional structure of the putative amino acid sequence of the endoglucanase from A. fumigatus DBiNU-1 (Additional information section, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation